تسجيل نوع من الديدان الخيطية Hysterothyla cium aduncum (Nematoda: Anisakidae) المتطفلة على أسماك القجاج Sparus aurata في المياه البحرية لساحل اللاذقية - لايقة, تغريد (Latakia University Journal -Biological Sciences Series, 2018)
This study aimed to investigate the Endoparasites in Sparus aurata in the Lattakia marine waters. A total of 54 individuals of Sparus aurata were collected between October 2015 and September 2016 from different localities from the coast of Lattakia between Ras Al Baseet and Iben Hani. Internal organs (stomach, intestines and body cavities) for all individuals caught fish were examined for parasitic infection. We isolated the parasite Hysterothylacium aduncum that belongs to the Nematodes from the stomach and intestines of Sparus aurata. The results showed that the highest rate of infection with this isolated parasite was in the summer, which amounted to 25% and has coincided with high temperature. During this research, the parasite was isolated for the first time from Sparus aurata, which caught in the Syrian marine waters. هدف البحث إلى التقصي عن الإصابة بالطفيليات الداخلية لدى سمك القجاج Sparus aurata في المياه البحرية لساحل اللاذقية. جمع 54 فرداً من أسماك القجاج خلال الفترة الممتدة بين تشرين الأول 2015 وأيلول 2016 من مواقع صيد مختلفة من شاطئ محافظة اللاذقية بين رأس البسيط وابن هاني. فحصت الأعضاء الداخلية (المعدة، الأمعاء وتجاويف الجسم) لجميع الأفراد المصطادة للكشف عن الإصابة بالطفيليات. عزل الطفيلي Hysterothylacium aduncum الذي ينتمي إلى الديدان الخيطية من معدة وأمعاء سمك القجاج المدروس. وقد أظهرت النتائج أن أعلى نسبة إصابة بهذا الطفيلي المعزول كانت في فصل الصيف والتي بلغت 25% وقد تزامن ذلك مع ارتفاع درجة الحرارة. خلال بحثنا الحالي تم عزل هذا النوع الطفيلي للمرة الأولى من أسماك القجاج Sparus aurata المصطادة في المياه البحرية السورية.